The Coaching Management of Boxing Achievement in PERTINA East Nusa Tenggara Province - Dawi, Figinus Konradus; Soegiyanto, Soegiyanto; Irawan, Fajar Awang (Journal of Physical Education and Sports, 2020)
This research aims to analyze and describe The Coaching Management of Boxing Achivement in PERTINA East Nusa Tenggara Province. This research aims to analyze planning, organizing, actuating and controlling of the program. This study used a qualitative approach with an ethnographic design with George R. Terry’s POAC model. The subjects in this study were administrators, coaches and athletes at the PERTINA East Nusa Tenggara Province. The results of this research are: Planning in terms of planning was good because according to the standards set, Organizing as a whole was not good because the arrangement of infrastructure and funding is not maximal, Implementation (Actuating) was not good because of limited facilities infrastructure and funding are still minimal and controlling, overall was less good because the supervisory commission did not carry out routine controlling.